The Poncho Lamina Technique: A Protocol for Hard and Soft Tissue Augmentation in Atrophic Ridges Receiving Adjacent Implants - Alexander Tzovairis; Marius Leretter; Bart Vandenberghe; Roberto Rossi (Medicina, 2023)
The current scientific knowledge and guidelines in bone and soft tissue augmentation suggest the use of staged surgical workflows as the gold standard of regenerative procedures during implant therapy. In this context, the process is always the same, regardless of the techniques applied: an alternate series of surgical acts that follow one another after the completion of a specific period of osseointegration or graft maturation. As a result, the overall surgical treatment is often long and invasive and induces scar tissue formation. This article proposes a novel, fast, and less-invasive biphasic protocol with the use of a well-documented cortical barrier mounted on healing screws that are further replaced by customized abutments at an early second stage. Two cases are reported, one for an upper maxillary edentulous area and the other for a mandibular, with a total of four implants placed. The results at 4 months postop showed an optimal soft tissue configuration for both cases, with adequate cervical profile generation and a sufficient supracrestal complex height above the implant platforms. Significant bone gains were also recorded through CBCT data collection, either with alveolar width measurements on axial slices, the superposition of pre-op and post-op datasets, or 3D visualization after bone volume segmentation.